“Watch me - this is how it should be done!”: the effect of normative language on preschoolers’ overimitation occurs only in the lab but not at home - Bach, Jule; Pauen, Sabina (Journal of experimental child psychology, 2026)
Preschoolers often imitate actions that are causally irrelevant, a phenomenon called “overimitation (OI)”. The present study examines how task context and language framing influence OI. A total of 160 four- to five-year-old German children from predominantly middle- to high-socioeconomic backgrounds participated in the study. All children performed the same OI task under four different conditions. They observed an adult model who demonstrated functional and non-functional actions before they themselves were allowed to retrieve a cookie from a transparent jar which could easily be opened by unscrewing the lid. This task was conducted either in a laboratory setting with an unfamiliar experimenter as model or at each child’s home with their caregiver as model. In both contexts, either a normative or a non-normative verbal instruction was used, resulting in a 2 × 2 between-subjects design. OI scores were not significantly affected by framing or context alone. However, a significant interaction was found between the two factors: a normative language led to more OI in the lab-context, but did not affect OI-scores in the home context. Implications of these findings for children’s sensitivity to context conditions and language framing in observational learning are discussed.
Online verfügbar: 17. Oktober 2025
Gesehen am 02.12.2025